Washing souls, washing bodies: practice of baptism in the parish of the city of Natal, century XVIII e XIX - Nascimento Torres de Paula, Thiago (Em Perspectiva, 2017)
In the catholic western world in the Antique Regime, all newborn babies, obligatory, had to be baptized. Therefore, the aim of this research is to analyse the practice of baptism in the social formation of the Parish of the city of Natal, between the 1700s and 1800s, establishing connections with other social figurations in Portuguese and Spanish America. For this, the sources investigated were: the documents of baptism, documents of death, the first registry book of the Mother Church of Nossa Senhora da Apresentação, among others. Everything analysed in the light of Social History referencial.